A Review of Training Protocols for Preventing Anterior Cruciate Ligament Injuries in Soccer Players - Moosareza Ghorbani; Mostafa Varmaziar; Mona Heydarian (Biyumikānīk-i varzishī, 2025)
Objective Anterior cruciate ligament (ACL) injuries are among the most common injuries in athletes, particularly soccer players. While numerous studies have examined the effectiveness of injury prevention programs for ACL injuries across various sports, no study was found that specifically reviewed training protocols for ACL injury prevention in soccer players. Therefore, the aim of this study was to review training protocols designed to prevent ACL injuries in soccer players. Methods This systematic review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles published between 2000 and 2025 focusing on ACL injury prevention were searched. Relevant articles were identified using both English and Persian keywords, including: prevent ACL injury, knee injury prevention, prevention of knee injuries, injury prevention in soccer, knee prevention, neuromuscular training, injury prevention programs, neuromuscular intervention, prevention of ACL injuries, prevention of knee injuries in soccer, lower limb injury prevention, and soccer injury prevention programs. The search was carried out in both Persian and international databases, including Magiran, Medlib, ISC, SID, PubMed, Google Scholar, PEDro, Scopus, ScienceDirect, and Irandoc. Results After applying inclusion and exclusion criteria, a total of 20 articles were selected. Among these, 10 studies focused on general warm-up routines, while the remaining 10 investigated neuromuscular training programs. Conclusion ACL injury prevention programs incorporating both general warm-up routines and neuromuscular training appear effective in reducing the incidence of ACL injuries among soccer players. However, no single comprehensive program has yet been shown to be effective across all age groups and populations. A notable strength of these interventions is that none have been associated with an increased risk of injury. Nevertheless, due to the complexity and challenges involved in combining various exercise types, it remains difficult to definitively determine the superiority of one approach over another.